Contributing Factors Impacting Project Successfulness - Tanmay Bhosale; Aniket Pawar; Anagha Shinde (ASEAN Journal of Science and Engineering, 2022)
This research paper comprises three different case studies taken under consideration and involves a step-by-step analysis of all three. The analysis of these case studies is based on the fundamentals of Project Management Techniques and the way it was implemented by the Project Managers during the different phases of the project to achieve success. The purpose of this research is to study the projects which avoided failure even at the toughest times and proved any project can be successful if managed and executed with proper project management techniques. The methodology used for conducting this research was Interview methodology aligned with the Case study approach. Project Managers of the mentioned projects were interviewed to accumulate accurate and authentic information to analyze, discuss and reach conclusion. Overall, the reason behind the study is to demonstrate that under appropriate guidance by project managers and the use of relevant project management techniques, factors leading to project failure could be identified and mitigated to ensure success.